Mobile Wallets Gateway For Cashless Payment (Journal of Pharmaceutical Negative Results, 2023)
Smart phones are an integral part of peoples' daily lives in the modern world. Smart phones are now gadgets where mobile users can conduct financial transactions or make payments utilizing a phone-installed application thanks to technical improvement. The current purpose is to explain the mobile wallets concept , mobile wallets functions, mobile wallet types and their benefits. Moreover, usage of mobile wallets by various companies has been described. It also aims to highlight various factors that influence consumers' decisions to adopt mobile wallets as well as risks and challenges that are faced by mobile wallet users.Data from 100 respondents were gathered using a standardized questionnaire.